Analyzing Cross-Linguistic Influence in Second Language Acquisition : A Bibliometric Study Using Vosviewer - Ratnasari Ratnasari; St. Asriati. Am; Dian Tanri Wulan; Syahruni Syahruni (Universitas Muhammadiyah Enrekang, 2024)
This study aimed to determine the bibliometric data analysis of Cross Linguistic Influence in Second Language Acquisition using VOSviewer. It obtained the data through a reference management application. It used the keywords